Deep Learning–Based Analysis of Soybean Crop Growth Using Sentinel-2 Vegetation Indices - Rahul B. Mannade (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Remote sensing has become an important technology for crop development monitoring and assessment of vegetation health of current agriculture systems. By combining satellite imagery with advanced data analysis techniques, researchers are able to observe crop conditions on a large scale of agricultural areas with greater efficiency. In recent years, deep learning methodologies have shown a great potential for the decomposition of complex interrelationships between spectral characteristics and crop physiological attributes. The current investigation uses a framework of deep learning to study the growth of soybean using vegetation indices extracted from Sentinel 2 satellite imagery. The field experiment was conducted on a 4 acre soybean field located in Sillod region Maharashtra, India & used Sentinel 2 Multispectral Data collected on 1st October 2022 and 26th October 2022 to determine the temporal variations in crop status. Vegetation indices were extracted from the satellite imagery, Normalized Difference Vegetation Index (NDVI), Green Normalized Difference Vegetation Index (GNDVI), Normalized Difference Red Edge Index (NDRE) and Chlorophyll Index Green (CIgreen) were used to quantify vegetation vigor and chlorophyll activity. A deep learning autoencoder was used to determine latent vegetation features from these indices and identify hidden patterns of crop growth. A resulting model yielded two latent variables, which contained crop condition characteristics for two observation dates. Discernible temporal changes in soybean canopy condition were indicated from analysis of the latent features. DeepFeature1 had a small increase from 0.053 to 0.067 while DeepFeature2 showed a significant decrease from 1.0137 to 0.7911 between the two measurement occasions. The attenuation of DeepFeature2 represents a drop in the vigor and activity of the vegetation and the chlorophyll of the soybean plant at a later stage of its growth. These observations follow the expected phenological path of soybean crops approaching maturity. Consequently, the results validate that the feature extraction with deep learning could be effective for capturing temporal dynamics of crop growth using the vegetation indices derived from satellite remote sensing, and provides nice information for agricultural monitoring and precision farming practices. DOI: https://doi.org/10.17762/ijisae.v10i3s.8088